2010
DOI: 10.1073/pnas.1005830107
|View full text |Cite
|
Sign up to set email alerts
|

Structure of bacterial LigD 3′-phosphoesterase unveils a DNA repair superfamily

Abstract: The DNA ligase D (LigD) 3′-phosphoesterase (PE) module is a conserved component of the bacterial nonhomologous end-joining (NHEJ) apparatus that performs 3′ end-healing reactions at DNA double-strand breaks. Here we report the 1.9 Å crystal structure of Pseudomonas aeruginosa PE, which reveals that PE exemplifies a unique class of DNA repair enzyme. PE has a distinctive fold in which an eight stranded β barrel with a hydrophobic interior supports a crescent-shaped hydrophilic active site on its outer surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 27 publications
3
62
0
Order By: Relevance
“…To determine the role of the LigD-PE domain in the repair of chromosomal damage, we studied M. smegmatis carrying LigD with inactivating mutations in the LigD-PE domain, LigD-E310A and -H336A. The E310A substitution abolishes only phosphomonoesterase activity, whereas the H336A substitution abolishes both phosphomonoesterase and phosphodiesterase activities (19,23,24). Stationary-phase IR experiments indicated that PE inactivation through either mutation conferred a small but statistically significant sensitization to IR of approximately 5-fold at 1,200 Gy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the role of the LigD-PE domain in the repair of chromosomal damage, we studied M. smegmatis carrying LigD with inactivating mutations in the LigD-PE domain, LigD-E310A and -H336A. The E310A substitution abolishes only phosphomonoesterase activity, whereas the H336A substitution abolishes both phosphomonoesterase and phosphodiesterase activities (19,23,24). Stationary-phase IR experiments indicated that PE inactivation through either mutation conferred a small but statistically significant sensitization to IR of approximately 5-fold at 1,200 Gy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Atomic structures have been determined for the POL and LIG domains of bacterial LigD proteins bound to substrates at various functional states along their respective reaction pathways (Shuman and Glickman, 2007). On the other hand, only recently has the PE domain been characterized structurally (Nair et al, 2010). …”
Section: Biological Contextmentioning
confidence: 99%
“…We recently reported the 1.9 Å crystal structure of the active phosphodiesterase core of Pseudomonas aeruginosa PE ( Pae PE), spanning residues 30-187 (Nair et al, 2010). Pae PE has a novel fold in which an 8 stranded β-barrel with a hydrophobic interior supports a crescent-shaped hydrophilic active site on its outer surface.…”
Section: Biological Contextmentioning
confidence: 99%
“…Many archaeal species survive in some of the most extreme environments on the planet, and therefore it is important to investigate how they maintain genome stability to understand how life evolved in the hostile conditions present on the primordial earth and how these organisms continue to thrive in extreme terrestrial niches. Although some NHEJ-like genes have been identified in archaea (9,(16)(17)(18), a complete DNA-break repair apparatus has not been reported. Therefore, it is unclear if a related DSBrepair pathway operates in archaea.…”
mentioning
confidence: 99%